The clarification and retention of zinc and manganese from raw water by alginate and carrageenan - (:unkn) unknown (My University, 2006)
In this work was investigated the clarification and uptake of zinc and manganese with a mixture of alginate and aluminum sulfate / carrageenan in raw water. The best results were obtained with aluminum sulfate 12 ppm and alginate sodium 10 ppm where NTU value was decreased to 2.4. The uptake of metals by algal polysaccharides were 22.9 ppb Zn and 30.48 ppb Mn for aluminum sulfate 12 ppm + sodium alginate 10 ppm and 27.53 ppb Zn, 7.49 Mn for 5 ppm carrageenan. Thus it was concluded that sodium alginate effectively binds Mn while Zn by carrageenan.